Augmenting landmarks during the head-up provision of in-vehicle navigation advice - Large, David R.; Burnett, Gary; Bolton, Adam (IGI Global, 2017)
The use of landmarks during the provision of directions can greatly improve drivers’ route-following performance. However, the successful integration of landmarks within in-vehicle navigation systems is predicated on the acquisition and deployment of good quality landmarks, as defined by their visibility, uniqueness, permanence, location etc., and their accurate and succinct depiction on in-vehicle displays and during accompanying verbal messages. Notwithstanding the inherent variability in the quality and propensity of landmarks within the driving environment, attending to in-vehicle displays and verbal messages while driving can distract drivers and heighten their visual and cognitive workload. Furthermore, vocal utterances are transient and can be littered with paralinguistic cues that can influence a driver’s interpretation of what is said. In this paper, a driving simulator study is described aiming to investigate the augmentation of landmarks during the head up provision of route guidance advice – a potential solution to some of these problems. Twenty participants undertook four drives utilising a navigation system presented on a head up display (HUD) in which navigational instructions were presented as either: conventional distance-to-turn information; on-road arrows; or augmented landmarks (either an arrow pointing to the landmark or a box enclosing the landmark adjacent to the required turning). Participants demonstrated significant performance improvements while using the augmented landmark 'box’ compared to the conventional distance-to-turn information, with response times and success rates enhanced by 43.1% and 26.2%, respectively. Moreover, there were significant reductions in eyes off-the-road time when using this approach, and it also attracted the lowest subjective ratings of workload. We conclude that there are significant benefits to augmenting landmarks during the head-up provision of in-car navigation advice.